Let $X$ be a positive random variable with density function $f$ and $\mathbb{E}X<\infty$, let $a>0$ such that $a\cdot\mathbb{E}X<1$. Denote the Laplace transform of $f$ by $$\hat{f}(s)=\int_0^{\infty}e^{-sx}f(x)dx.$$ I don't understand why the following inequaltiy holds: $$a\left(\frac{1}{s}-\frac{\hat{f}(s)}{s}\right)<1~~\forall s>0$$

  • 1
    $\begingroup$ $\frac{1-\hat{f}(s)}{s}$ is the Laplace transform of $1_{x > 0}-\int_0^x f(t)dt $ $\endgroup$
    – reuns
    Apr 12, 2017 at 21:39
  • $\begingroup$ @user1952009 So I have $$a\left(\frac{1-\hat{f}(s)}{s}\right)=a\left(\int_0^{\infty}e^{-sx}(1-F(x))dx\right)\leq a\int_0^{\infty}1-F(x)dx=a\mathbb{E}X<1$$ for all $s>0$ $\endgroup$
    – Vroko
    Apr 13, 2017 at 8:54
  • $\begingroup$ Positive random variable means $P(X < 0) = 0$ ? then yes, $\int_0^\infty (1-F(x))dx = \mathbb{E}[X]$. Can you write an answer, proving everything ? $\endgroup$
    – reuns
    Apr 13, 2017 at 17:56
  • $\begingroup$ @user1952009 This one is all over the site already... $\endgroup$
    – Did
    Apr 15, 2017 at 20:01

1 Answer 1


Since $\hat{f}(s)=\int_0^{\infty}e^{-sx}f(x)dx=s\int_0^{\infty}e^{-sx}F(x)dx$ we get $$\int_0^{\infty}e^{-sx}(1-F(x))dx=\frac{1-\hat{f}(s)}{s}$$ and therefore $$a\left(\frac{1-\hat{f}(s)}{s}\right)=a\left(\int_0^{\infty}e^{-sx}(1-F(x))dx\right)\leq a\int_0^{\infty}1-F(x)dx=a\mathbb{E}X<1.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.